New curcumin analog, CCA-1.1, synergistically improves the antiproliferative effect of doxorubicin against T47D breast cancer cells - Febri Wulandari; Muthi' Ikawati; Dhania Novitasari; Mitsunori Kirihata; Jun-ya Kato; Edy Meiyanto (Universitas Gadjah Mada, 2020)
An improved compound of pentagamavunone-1 (PGV-1), chemoprevention-curcumin analog 1.1 (CCA-1.1), has been synthesized and proven to have antiproliferative effects against breast cancer cells. This study is designed to investigate the potency of CCA-1.1 alone and in combination with doxorubicin (Dox) on T47D cells in comparison with that of PGV-1. We used the MTT assay to assess cytotoxic activity. Propidium iodide (PI), annexin-V-PI, and DCFDA staining were respectively used to determine cell cycle profiles, apoptosis, and intracellular reactive oxygen species (ROS) levels. Senescent cells were identified using the SA-b-galactosidase assay. Our results revealed that CCA-1.1 possesses cytotoxic effects similar to those of PGV-1 on T47D cells. Synergistic effects during co-treatment with Dox were also observed. CCA-1.1 arrested cell cycle progression at the G2/M phase and limited sub-G1 accumulation, which is correlated with apoptosis. CCA-1.1 alone and in combination with Dox increased senescence and intracellular ROS to a similar level to those achieved by PGV-1. CCA-1.1 alone and in combination with Dox enhanced cytotoxic activity toward T47 cells compared to PGV-1. Thus, this curcumin analog may be a potential chemotherapeutic/co-chemotherapeutic candidate for estrogen receptor-positive (ER+) breast cancer therapy.